PREDIKSI PRODUKSI PADA VENDOR MANAGED INVENTORY (VMI) DENGAN MENERAPAN RADIO FREQUENCY IDENTIFICATION (RFID) DAN FUZZY TIME SERIES (FTS) - Mashuri, Chamdan (Inovate, 2019)
Inventory is a material deposit of a company in the form of raw materials, in-process goods and finishedgoods. Inventory is also a major factor in the center of corporate activity, one of which is influenced bydemand or sales. Vendor managed inventory (VMI) is one of inventory control system that is very useful toimprove company performance. This research uses Radio frequency identification (RFID) technology anduses fuzzy time series (FTS) method to predict demand or sales and leverage vendor managed inventory(VMI) model or system in which to apply formula for safety stock control which then developed bymodeling business and Implemented in the form of web-based information systems. By using the actualhistorical data of sales for 5 years which then predicted by fuzzy time series method, and from predictionresult is calculated for safety stock. By using 60 sample data from histori penjulan obtained Mean AbsoluteDeviation (MAD), Mean Square Error (MSE) and Mean Square Percent Error (MAPE) are 50,690,4,600,953,015 and 15%. From the prediction results used for the calculation of safety stock in December2106 obtained value of 135,535. This indicates that the fuzzy time series is good enough to be used inpredicting demand or sales and stock control..Keywords: VMI, Inventory, RFID, Fuzzy time series, Safety stock.